Design of CIM environment for automated wafer manufacturing process cell system - Channaiah B. Ramakumar. (2008)
This thesis focuses on the issues concerned with the design of Computer Integrated Manufacturing (CIM) environment based on Semiconductor Equipment and Materials International (SEMI) guidelines and SEMATECH standards framework used in shop floor information control system for wafer manufacturing process system.